(untitled) (Annals of Medical Research, 2022)
Aim: The aim of this study was to investigate the long-term complications of substance use on the vestibular system. Substance use disorders are thought to impair the vestibular apparatus as well as the auditory system. Materials and Methods: Sixty-five cases with a history of non-alcohol drug addiction who survived the withdrawal phase and 22 healthy controls were included in the study. The cases were categorized into 2 different subgroups as those who had used only opioids ("opioid") and those who had used an opioid and chemical simultaneously or otherwise ("opioid &chemical"). Vestibulospinal tests and video Head Impulse Test (vHIT) were performed on all participants and the results were analyzed. Results: A total of 65 (61 males/4 females, mean age was 25 ± 3.95 years) cases and 22 (males, mean age was 25 ± 3.3 years) healthy controls were included in the study. The mean age of the "opioid" group (n=33) was 25 ± 3.95 years, and the mean age of the "opioid & chemical" group (n=32) was 25 ± 3.13 years (p>0.05). When the cases and controls were evaluated according to vestibulospinal tests, a high level statistically significant difference was observed (p<0.001), but no significant difference was found according to vHIT. Conclusion: This is the first study evaluating long-term vestibular functions with the vHIT test in patients with substance use disorder. Although the results suggest that there is no vestibulo-ocular reflex (VOR) involvement in the groups according to the vHIT, it has been revealed that substance use has negative effects on balance and walking.